The unclothed body on and off stage in the Comedia Nueva - Thacker, J (Bulletin of the Comediantes, 2021)
This article examines the presence of the unclothed body in the comedia nueva, both when it appears on stage and when it is referred to off stage. It begins with a brief examination of what desnudez actually meant in practical terms in the corral theaters (and moralists' responses to states of undress). The study goes on to analyze in more detail some of the main implications and resonances of nakedness in the minds of Golden Age audiences. These are important for characterization, including the establishment of a character's poverty, madness, or vulnerability; for dramatists' attempts to establish time and place; and, above all, because of the eroticism of the unclothed body which is linked to pictorial traditions. Examples are taken from full-length comedias by a variety of playwrights, supplemented with the exploration of analogous motifs in seventeenth-century visual culture, to highlight its role in helping the audience imagine these scenes.